Anxiety associated with diagnostic uncertainties in early pregnancy. - Richardson, Alison; Raine-Fenning, Nick; Deb, Shilpa; Campbell, Bruce; Vedhara, Kavita (Wiley Online, 2016)
Objectives: To determine anxiety levels of women presenting to Early Pregnancy Assessment Units (EPAU) with abdominal pain and/or vaginal bleeding and assess how these change over time and according to ultrasonographic diagnosis.